STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI PONDOK PESANTREN DARUSSALAM KEPAHIANG - Ari Yanto; Aris Dianto; Dian Bastian; M. Effry Kurniawan (Department of Islamic Education Management, 2023)
Quality education must have good and competent human resources. Principals have an important role in improving the quality of education. The purpose of this study was to find out the strategies used by school principals to improve the quality of education. This research is a qualitative descriptive study conducted at Darussalam Kepahiang Islamic Boarding School. Research data obtained through interviews, observation, and documentation. From the results of the study it can be concluded that the strategy of the head of the Darussalam Kepahiang Islamic Boarding School in improving the quality of education is: (1) Improvement and Strengthening from within, by providing material at monthly coordination meetings. (2) Conduct Routine Supervision, by conducting class visits and analyzing the lesson plan that the teacher will use. (3) Evaluation of Teaching and Learning Activities (KBM), evaluation related to the ongoing learning process. (4) Teacher Discipline Development, through monthly meetings and direct reprimands. (5) Promotion on a regular basis, by distributing brochures, holding outreach to various parties, related agencies and institutions throughout Kepahiang Regency and its surroundings. (6) Improvement of Facilities and Infrastructure, such as the creation of new classrooms, computer laboratories, language laboratories, canteens, parking lots, sports fields. (7) Contextual Approach, an approach in the internal environment of Islamic boarding schools. (8) Selection of the right Principal with a complete understanding of the environment. (9) Optimizing the Implementation and Application of the Curriculum. (10) Stabilization of Environment and Schools and Culture of Islamic Boarding Schools (11) Organizing classes.